THE IMPACT OF VIDEO GAMES ON READING ABILITY AS AN EARLY INDICATION OF DYSLEXIA - Aa Qonaatun; Rifki Mulyana; Lia Amalia (Jurnal Cinta Nusantara, 2025)
The objectives of this study was conducted to know; physiological factors from the impact of playing video games on reading ability as an early indication of dyslexia, intellectual factors from the impact of playing video games on reading ability as an early indication of dyslexia, environmental factors from the impact of playing video games on reading ability as an early indication of dyslexia, and psychological factors from the impact of playing video games on reading ability as an early indication of dyslexia. This study used qualitative research with descriptive approach. Qualitative research involves the use of data collection techniques such as document analysis, observation, and interviews. Then analyzed using triangulation analysis techniques. The data analysis methodology for this study is based on the 'Reading Ability' model put forward by Lamb and Arnold in 1976. They emphasized that reading ability has four factors, namely physiological factors, intellectual factors, environmental factors, and psychological factors. The result showed that the impact of playing video games can cause a decrease in reading ability, this is due to physiological factors in which students experience problems with their vision. This may indicate early symptoms of dyslexia. The intellectual factor in playing video games has an impact on their intelligence abilities, however, if it is not balanced with the learning process carried out through written media it can cause problems in writing words which results in their understanding of letters interfering with their reading abilities. And if left untreated, this could indicate dyslexia. Environmental factors can have an impact on children playing video games which can lead to children's lack of reading ability which is at risk of being categorized as an early indication of dyslexia. Children's psychological factors resulting from playing games can cause children's motivation and interest in learning to read to decrease, this is because children's emotional stability is disturbed to the point that they can limit themselves in socializing with peer groups. Keywords: Reading Ability, Video Games, Dyslexia